A Study of the Factors Influencing Information Literacy on Farmers' Willingness to Participate in E-Commerce: the Mediating Effects of Perceived Benefits and Perceived Risks, and the Moderating Effect of Government Support - MA Ning, ZHANG Xiaoyi, LIU Qixuan (Nongye tushu qingbao xuebao)
[Purpose/Significance] Promoting the digital transformation of agricultural product circulation through e-commerce has become a crucial way for rural revitalization in China. For three consecutive years, China's No. 1 Central Document has listed the high-quality development of agricultural e-commerce as a priority for upgrading the level of rural industrial development. However, persistent disparities in information literacy and imbalance in risk-benefit perceptions among farmer groups constrain the effective popularization of e-commerce platforms for agricultural products. To address this issue, this study integrates the Theory of Planned Behavior (TPB) and the perceived benefit-risk theory to construct a conceptual framework. It explores the relationship pathways among information literacy, perceived risks, perceived benefits, government support, and farmers' willingness to participate in e-commerce, aiming to provide theoretical insights for governments and enterprises to deepen the high-quality development of agricultural e-commerce business and rural revitalization. [Method/Process] Based on the above background, this paper integrates and proposes a conceptual model that includes the relationship of five potential variables: information literacy, perceived benefits, perceived risks, government support and engagement intention, based on the theory of planned behaviour and the theory of perceived benefits-perceived risks. In order to ensure the appropriateness of the sample distribution as well as the convenience, authenticity and reliability of the data collection, this study used a combination of online (WeChat group of village committees) and offline (recruiting home-based university students for field survey) to collect questionnaires from farmers across the country, and a total of 730 valid farmers' sample data were collected. Finally, based on the above data, the direct paths of perceived benefits, perceived risks and farmers' information literacy on farmers' willingness to participate in agricultural e-commerce were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). We focus our analysis on verifying the mediating roles of perceived benefits and perceived risks, as well as the moderating role of government support, in enhancing farmers' willingness to participate in agricultural e-commerce. [Results/Conclusions] The findings reveal that increased information literacy strengthens farmers' willingness to engage in agricultural e-commerce. Most farmers prefer participation scenarios with high perceived benefits and low perceived risks, where government support plays a key role in endorsing and leading trust. In this regard, local governments should establish tiered training systems and risk-hedging mechanisms (e.g., agricultural insurance, logistics subsidies) to address age-specific demand for information literacy improvement in rural areas and mitigate operational risks. We suggest actively publicizing national high-quality rural e-commerce demonstration cases and improving the perception of benefits to motivate farmers to participate, so as to achieve the high-quality development of agricultural e-commerce in a multi-initiative way. In addition, future research should pay more attention to the breadth of the sample coverage and the depth of the sample research process, and consider using all offline field research to further examine the impact of regional differences and the differences in the digital characteristics of the new farmers (Generation Z) on their willingness to participate in e-commerce. This will provide empirical evidence and guidance for rural revitalization and high-quality development of agricultural e-commerce.